Navigating Virtual Environments – Do Physical Rotations Aid in Orientation? - Kitson, Alexandra; Grechkin, Timofey Y.; Heyde, Markus von der; Riecke, Bernhard E. (Second International Workshop on Models and Representations in Spatial Cognition, 2017)
Physical motions may help maintain self-orientation in virtual environments compared to a situation where only visual information is available. However, it remains unclear how much and what kind of motion is required to significantly increase performance. In this study, participants (N=15) navigating through a virtual maze had to discover and remember seven target objects and later point to them from different locations along the path. We compared two locomotion conditions: (1) visual-only, where participants sat on a non-rotating chair and used the joystick for both forward movement and rotation; and (2) physical rotations, where participants physically rotated on a swivel chair to change direction of travel (as determined by the Head Mounted Display’s gaze direction) and controlled forward movement via joystick. Spatial orientation performance was quantified as pointing error, absolute ego-orientation error, and configuration error. Unexpectedly, we found no benefit of physical rotation: pointing consistency was better for the visual only condition, F(1, 60) = 5.160, p = .027, η2 = .079 – at least for the first three turns in males, and after a total of 120 degrees of turning, participants were completely disoriented. Furthermore, females showed larger difficulties in maintaining self-orientation (ego-orientation error) than males, F(1, 60) = 5.110, p = .027, η2 = .078, expanding prior research findings demonstrating gender differences in navigation studies. We hypothesize this lack of a benefit from physical rotation might be related to the inconsistency of using body movements only for rotations, but not translations. This suggests that embodied interfaces should include at least some physical translation or translational motion cueing. These findings inform our ongoing effort to develop prototype navigation interfaces.
Keywords: Riecke; Riecke_2017; alex-kitson; bernhard-riecke; leaning-based interfaces; markus-von-der-heyde; motion-cueing; naviChair; poster; posterWithoutPaper; proj--motionCueingInterfaces; talkWithoutPaper; timofey-grechkin